Pengaruh Tinggi Back Rest Roller Terhadap Mutu Kain Tenun Grey di Mesin Tenun Air Jet Loom Pada Industri Tekstil - Rana Ardila Rahma (LPPM Politeknik LP3I Medan, 2021)
In the weaving process, the re-positioning of the back rest roller is carried out in order to produce the right tension of the warp thread according to the fabric construction to be made and to open a clean warp mouth opening in order to produce a smooth feed post during the process. However, with the development of science, it is known that the appropriate rearrangement of different back rest roller will also affect the quality of the fabric produced. This research was conducted to see the quality of the fabric produced with different back rest roller heights on the Air Jet Loom weaving machine at PT Malakasari Textile Mills. So that it get the right height of the roller height for good quality fabric according to company needs. Observations and tests are carried out at the height of the roller rest height by adjusting different heights, there are at the heights of –1, +1, and +3 by manually raising and lowering the back rest roller so that different types of fabric samples with same construction are produced. Then the fabric sample produced is then tested on the tensile strength and stretching of the fabric towards the warp, the tear strength of the fabric towards the thickness of the fabric, and the air permeability of the fabric. Based on the results of research and statistical calculations using one-way ANOVA, it turns out that there are differences in the quality of all fabrics produced and it is found that at setting the rear height at position -1 produces the best quality fabric in terms of fabric strength. stretch of the fabric towards the warp, and the tear strength of the fabric towards the weft, with respective amounts of 310.94 N, 18.24%, and 6.30 N. However, setting the rear height at the +3 position is the most appropriate for the quality of the fabric includes the thickness of the fabric and the permeability of the fabric, with the respective sizes are 0.322 mm and 70.60 cm3/cm2/s. So it can be concluded that there are advantages and disadvantages of the various heights of the back rest rollers used for the quality of the fabric produced.